2020
DOI: 10.1037/pne0000195
|View full text |Cite
|
Sign up to set email alerts
|

Executive functions and intelligent goal-directed behavior: A neuropsychological approach to understanding success using professional sales as a real-life measure.

Abstract: Executive functions are proposed to underpin intelligent goal-directed behavior. Such skills, linked through multiple neuropsychological studies to functioning of the frontal lobes, are theorized to predict achievement in nonroutine activities. Furthermore, patients with frontal lobe damage often display disorganized behavior and real-life failures such as employment instability and bankruptcy despite normal or superior intelligence. These observations suggest that executive ability should predict real-life su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 80 publications
0
4
0
1
Order By: Relevance
“…Ecological tasks, such as the Hotel Task (Pluck et al, 2020) and EcoKitchen (Júlio et al, 2019), were found even less frequently. In general, ecological tasks simulate everyday activities, with the patient’s behavior being observed during their performance in a standardized/controlled environment.…”
Section: Discussionmentioning
confidence: 99%
“…Ecological tasks, such as the Hotel Task (Pluck et al, 2020) and EcoKitchen (Júlio et al, 2019), were found even less frequently. In general, ecological tasks simulate everyday activities, with the patient’s behavior being observed during their performance in a standardized/controlled environment.…”
Section: Discussionmentioning
confidence: 99%
“…We used the same grading criteria. However, we substituted the eight English proverbs for eight Spanish proverbs that we have used in similar research previously (Pluck et al, 2020). The potential score range was from 0 to 32, higher scores indicating better performance.…”
Section: Methodsmentioning
confidence: 99%
“…A su vez, con apoyo de Aronsson (2020 citado en Arias y Batista, 2021), es posible declarar que la acción de conectar la diplomacia científica con las neurociencias, se constituye en un deseo de la sociedad contemporánea, debido a la necesidad imperante de que la diplomacia se fundamente aún más en la evidencia. Según Casaletto y Heaton (2017); Pluck, et al (2020) la sociedad actual demanda la resolución de problemas por pandemias desde un enfoque sistémico, a partir de los aportes de distintas disciplinas (ver Figura IV), por ello, se De la literatura analizada, distintos autores declaran que una gran cantidad de neurólogos, psicólogos y diplomáticos señalan la importancia de construir una ruta que conecte la diplomacia científica con las neurociencias; además enfatizan en que esta relación irá en aumento gracias a los descubrimientos en el campo de las neurociencias (Suyadi, 2019;Jiménez-Pérez et al, 2019citado en Arias y Batista, 2021. De ahí que Betts et al (2019 citado en Arias y Batista, 2021), manifiestan que tanto la mente (psicología), como el cerebro (neurociencia) y la cooperación (diplomacia) ofrecen una comprensión de prácticas que apoyan la negociación y la integración con base en evidencias.…”
Section: Entradaunclassified